Suicide Motif in Contemporary Polish Poetry - Škeljo, Đurđica Čilić (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
Distinctive and striking motif of suicide is present in contemporary Polish poetry in two ways, eitheras a discussion of or an announcement of one’s own suicide, or as a reflexion, that is, lyrical interpretationof the suicide of others. On the basis of the existentialist treatment of suicide as an authentic act, thearticle aims to analyse similarities and differences of poetic presentation of the aforementioned types ofsuicide — one’s own suicide, which always remains just an idea or a possibility, and other people’s suicide,which becomes an object of post festum lyrical interpretation.